2015
DOI: 10.4067/s0718-16202015000200011
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Citrus tristeza virus isolates in Chile are MCA13-positive and VT type, while mild isolates are MCA13-negative and T30 type

Abstract: Citrus tristeza virus (CTV) was reported in the 1960's to affect Meyer lemon trees in Chile, but no field symptoms were observed. This study performed a complete biological, serological and molecular characterization of one hundred CTV isolates obtained from different hosts and geographical origins. Decline symptoms (DI) were not found on trees grafted onto sour orange. In Pica Oasis in northern Chile, stem pitting (SP) was found to affect grapefruit and Mexican lime trees. Most isolates present in the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
6
1
Order By: Relevance
“…The presence of this strain on lemon was previously reported in neighbouring Uruguay, where it was referred to as "NC" (Benitez-Galeano et al 2015). The T30 genotype was previously reported on lemons in neighbouring Chile (Besoain et al 2015), however it was not found to be present among any of the populations in this study. We did not observe the divergent CTV strain from lemons in Greece described by Varveri et al (2015) (Figure 1 KC262793-L192GR).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The presence of this strain on lemon was previously reported in neighbouring Uruguay, where it was referred to as "NC" (Benitez-Galeano et al 2015). The T30 genotype was previously reported on lemons in neighbouring Chile (Besoain et al 2015), however it was not found to be present among any of the populations in this study. We did not observe the divergent CTV strain from lemons in Greece described by Varveri et al (2015) (Figure 1 KC262793-L192GR).…”
Section: Discussioncontrasting
confidence: 74%
“…Multiple molecular markers were used to characterize 100 CTV isolates from Chile, six of which were from lemon (Besoain et al 2015). Two of these were amplified with T30 specific primers, while the remaining four could only be amplified with universal primers, which cannot differentiate between CTV strains (T36CP) (Hilf et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…orchards. This syndrome, which causes low yield, quick decline, and premature tree deaths, has been associated with severe CTV like VT isolate, as reported by Besoain et al, Harper, Benítez-Galeano et al [1][2][3] In La Concepción, in Tihuatlán municipality, Veracruz, a sudden death that caused population decline of up to 50% of C. sinensis trees in less than three months was observed in 2018. In 2019, orchards of C. sinensis, C. reticulata, C. latifolia, and C. paradisi located in Alamo, Castillo de Teayo, Cazones, Cuitláhuac, Martínez de la Torre, Papantla, Tihuatlán, and Tuxpan municipalities were sampled to determine the presence and distribution of VT isolate.…”
Section: Introductionmentioning
confidence: 77%
“…In Chile, the first reports of the presence of important CGTD throughout the main citrus-growing area of the country were made by Weathers et al [11]. Later, Besoain [12] and Besoain et al [13] confirmed the presence of citrus tristeza, which is associated with aggressive CTV isolates in northern Chile and affects grapefruit and Mexican lime trees through the presence of stem pitting on the affected plants. Additionally, attenuated isolates of CTV in sweet orange and lemon trees were detected in central Chile.…”
mentioning
confidence: 99%
“…In a study carried out by Pizarro [16], at the Mallarauco locality close, it was determined that the cachexia incidence in this area varied between 10.3 and 36.7%; this area of the country was considered the most affected by this disease [15]. Although the reports by Weathers and collaborators were based on the symptoms observed in the field and with Mexican lima indicator plants, most modern reports have also used serological and/or molecular methods to diagnose the presence of these pathogens, especially CTV and cachexia isolates [12,13,16,17].…”
mentioning
confidence: 99%